The combination of mutations in BRAF and NRAS genes within a one tumor in patients with cutaneous melanoma - M. B. Aksenenko; A. S. Averchuk; T. G. Ruksha (Бюллетень сибирской медицины, 2019)
The paper provides a clinical description and analysis of two melanoma cases with mutations in the BRAF and NRAS gene within one tumor. Until recently, it was believed that mutations in the BRAF and NRAS genes are exclusive and do not occur within the same tumor. Later it was revealed that these mutations can exist within one tumor, but this is still quite a rare phenomenon. Molecular genetic analysis of the tumor obtained from both patients showed a mutation in the 15 exon of the BRAF gene c.1799T>A (V600E) and exon 2 of the NRAS p.G13S gene (p.37 G>A). The expression level of non-mutant NRAS protein was different in both cases. In conclusion, so in one patient, despite the presence of a mutation in the NRAS gene, the level of expression of the non-mutant protein was absent, which can be related to possible posttranscriptional disorders in the regulation of gene expression.